Pemanfaatan Internet sebagai Sumber Belajar Siswa pada Pembelajaran Geografi di SMAN 13 Padang - Syaiful, Fajri; Afdhal, Afdhal (Lembaga Yasin AlSys, 2025)
This study aims to examine the use of the internet as a learning resource for students in geography instruction at SMAN 13 Padang, identify the challenges encountered, and reveal the efforts made to address them. A qualitative method was used, with geography teachers and Grade XI Social Science 2 students as subjects. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that the internet facilitates students in finding geography learning materials, completing assignments, and accessing information not available in textbooks. Internet use occurred in three stages: planning based on the lesson plan (RPP), implementation by accessing materials such as natural disasters, and evaluation through observation of students’ participation, engagement, and curiosity. Challenges identified include slow internet connections, network disruptions due to power outages, depleted device batteries, and misuse of smartphones by students. To overcome these issues, teachers and students implemented various measures such as forming discussion groups, holding Q&A sessions and quizzes, and using alternative resources such as books. Additionally, students were guided to use the internet responsibly and resolve technical issues independently, such as restarting their devices. These findings indicate that despite technical and non-technical obstacles, the internet remains a valuable learning resource when supported by appropriate guidance and management strategies.